Wideband double-mode bulk acoustic wave resonator filters on lithium niobate using periodically slotted electrodes. (1st July 2022) - Wu, Ting; Wong, Yu-Po; He, Yi-Wen; Bao, Jing-Fu; Hashimoto, Ken-Ya
Abstract: This paper discusses applicability of periodically slotted electrodes for realization of wideband transversely coupled double-mode resonator filters using lithium niobate thin plates. First, two-dimensional analysis is carried out, and it is shown that the periodic structure is effective to control the frequency separation between two resonance modes, and synthesis of the fractional bandwidth larger than 24% is achievable. Next, three-dimensional analysis is performed for suppression of spurious resonances. It is shown that mass loading at the aperture edges is effective for piston mode operation, and transverse modes can be well suppressed. It is also pointed out that the bottom electrode should cover only the aperture region and be removed from the busbar and gap regions for suppression of unwanted resonances. With these proper edge treatments, spurious-free and wide passbands can be synthesized.